THE EFFECT OF PAIRED-STORY-TELLING TECHNIQUE ON THE SPEAKING ABILIITY OF THE SECOND YEAR STUDENTS OF SMP N 8 PEKANBARU - sutanti, Andriani; Azhar, Fadly; Novitri, Novitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The main objective of this study was to find out the effect of Paired-Story-Telling technique on the speaking ability of the second year students of SMP N 8 pekanbaru. This study was an experimental research with one group pre-test post-test design. The population of this research was the second year students of SMP N 8 pekanbaru. In this research, a single group was selected to be a sample by using cluster random sampling. The sample that has been choosen was class VIII.8 consisting of 39 students. a speakingl test was used to get the score of the students before and after taught by using Paired-Story-Telling technique. After all the data were collected, the writer calculated and analyzed them by using Microsoft excel 2010 and T-test formula. It was found that t-test score was 13.30 while t-table was 2.024. Since t-test was higher than t-table, it can be concluded that there is a significant effect of Paired-Story-Telling technique on the students’ speaking ability of the second year students of SMP N 8 Pekanbaru that can be seen from the t-test result and the improvement of the students’ scores in post-test.Keywords: Junior high school students,Speaking ability, Paired-Story-Telling technnique